Measuring and modeling of shrinkage characteristic naturalsoil in Kuantan Pahang - Siti Norhafizah, Japri (2012)
One of uses of clayey soil in engineering is as liner material. Natural soil containing clay minerals are often used as cheaper alternatives. Clayey soil undergoes shrinkage during drying with water content changes. Water content changes during wetting undergo swelling. Shrinkage cracks are major problem in many engineering construction. Liners that undergo excessive shrinkage behavior will caused the formation of cracks and create problems to the environment and human safety. In this study, the shrinkage behaviour of KB soil was determined during drying under zero applied stress. The volumes of soil specimens prepared at different water contents were measured using wax method. Additionally, the shrinkage curves were established using Kea and Gea model. The shrinkage curves enabled the determination of shrinkage limit of the soil as well as void ratios at consistency limits. The wax method was found to be useful in establishing the entire shrinkage characteristics of soils during the drying process. Similarly, the uses of parametric models provide continuous shrinkage curves with some limitations.